Application of two biomarkers for the analysis of DNA lesions on marine bivalves - Sotil, Giovanna (2006)
This work describes the standardization of Micronucleus Assay (MN) and Comet Assay techniques used for the evaluation of the DNA damage on marine bivalves. These techniques are important because they can evaluate the early stress response caused by pollutant agents and environmental changes. Branchial tissues of Semimytilus algosus and Aulacomya ater were used for in vivo and in vitro treatments. Tissues were exposed to the mutagenetic agents Mitomicine C in concentrations of 0,02; 0,04 and 0,06 x 10-6 M and H2 O2 in concentration of 100 μM evaluated at 1, 3, 6, 24 and 48 h. Different solutions for the tissue collection and cell isolation were evaluated, obtaining more cell viability with cold CMFS pH 7,3 saline solution. Micronucleus Assay were modified in the obtaining of suspension cell, we used 0,9% Sodium citrate hipotonic solution, fixation in methanol for seconds after the spread and dyed with 2% Giemsa. The Alkaline Comet Assay protocol described by Wilson et al. (1998) was standardized modifying the single-cell suspension embedded in LMP Agarose (1% in Kenny solution, pH 7,5), the exposure at lysing solution (pH 10 with DMSO and Triton) with changes from 1 to 16 h, electrophoresis in alkaline solution pH 13,7 and dyed with Ethidium bromide and Silver nitrate for agarose gels. Changes made at both techniques allowed us to obtain a high cell number with a defined morphology, recognizing macrolessions like the MN formation and nuclear aberrations, and the qualitative determination of microlessions observed by the fragmentation and migration of the DNA.